Medical Management of Hemorrhagic Bowel Syndrome in a Beef Bull - Joe S. Smith; Xueying Zhou; Paul T. Merkatoris; Cassandra A. Klostermann; Ryan M. Breuer (Case Reports in Veterinary Medicine)
A two and a half-year old Simmental bull was presented to Iowa State University’s Food Animal and Camelid Hospital for anorexia and lethargy of several days. Clostridium perfringens type A was identified via fecal culture and toxin genotyping. Hemorrhagic bowel syndrome (HBS) was diagnosed based on microbiological results along with abdominal ultrasonography, complete blood count, and serum biochemistry. Aggressive multi-modal therapy was employed including intravenously administered fluid therapy, potassium penicillin, lidocaine, flunixin, and pantoprazole among other supportive care. The bull was discharged after 15 days of hospitalization and recovered uneventfully to full function by the next breeding season. Currently all case reports with regard to HBS in beef cattle describe mortality. While the dairy cattle literature demonstrates that HBS has a high mortality rate, and suggests that surgical intervention has a higher prognosis when compared to medical therapy in dairy cattle. Our case would provide support to aggressive medical treatment for HBS in beef cattle.